774 TEAM DYNAMICS AND CLINICIAN'S PERSONAL BELIEVES IN TREATMENT OPTIONS INFLUENCE MULTIDISCIPLINARY TREATMENT DECISION-MAKING DURING AN ONCOLOGIC UPPER GASTROINTESTINAL MULTIDISCIPLINARY TEAM-MEETING. (17th September 2021) - Luijten, Josianne; Westerman, Marjan; Vissers, Pauline; Verhoeven, Rob; Nieuwenhuijzen, Grard
Abstract: : The probability of undergoing treatment with curative intent according to the hospital of diagnosis has been shown to vary considerately for esophagogastric cancer affecting survival negatively. Little is known which factors attribute to this variation. The aim of this study is to investigate the possible differences in clinical decision-making (CDM) during the multidisciplinary team meeting (MDTM). Methods: A mixed method study design consisting of quantitative and qualitative data was conducted in which thematic content analysis of the current sub-study focused on the 16 MDTM observations and transcripts of 30 semi-structured interviews with clinicians was performed. Interviews were transcribed ad verbatim and coded. Seven focus groups were held to enrich, further explore and validate the gathered data. Results: Clinician's personality traits including ambition and the intention to be innovative were mentioned as facilitators, whereas hierarchy was mentioned as a barrier in CDM. Physician's believes in a certain treatment and previous experiences with treatment outcomes and team dynamics within the MDTM influenced CDM. A continuum was identified in which at one end hospitals tended to be more guideline and evidence minded and at the other end of the continuum hospitals tended to search for boundaries maximizing chances of curation. All hospitals took patient characteristics in consideration. Conclusion: Mechanisms influencing decision-making consisted of following guidelines, using evidence-based medicine, searching for boundaries, and taking patient characteristics into consideration. Nevertheless, the extend in which hospitals involved these mechanisms in their CDM differed. Variation in team dynamics was observed and awareness should be created that these factors attribute to CDM during an MDTM.